The reasoned schemer - Friedman, Daniel P. (MIT Press, 2005)
"Adding logic capabilities required the introduction of new forms. The authors' goal is to show to what extent writing logic programs is the same as writing functional programs using these forms. In this way, the reader of The Reasoned Schemer will come to understand how simple logic programming is and how easy it is to define functions that behave like relations."--BOOK JACKET.
Includes index.
Keywords: Scheme (Computer program language); elektronické knihy; electronic books